Labour Market Profile, Previous Employment and Economic Integration of Refugees: An Austrian Case Study - Bernard Rengs; Johannes Kopf; Isabella Buber-Ennser; Judith Kohlenberger; Roman Hoffmann; Michael Soder; Marlies Gatterbauer; Kai Themel (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2017)
In 2015, large numbers of forced migrants crossed the borders to the European Union and the influx of new arrivals has led to the important question of implications for the host societies. This article assesses the labour market profile and previous employment of the recent inflows of displaced persons, mainly coming from Syria, Iraq and Afghanistan. Moreover, sectoral unemployment rates and trends in job openings in different economic branches in the host society are compared to the profiles of the refugee population. Analyses are based on two unique datasets on displaced persons in Austria: DiPAS (a social survey among asylum seekers) and competence checks (information on occupational and transferable skills). Results indicate that the labour supply provided by refugees' roughly corresponds to the labour demand in Austria. In terms of a potential impact on the Austrian labour market, this match might be regarded as favourable.
Keywords: 300; Austria; displaced persons; labour market participation; skills